Assessing the potential of the qualitative trajectory calculus to detect gait pathologies: a case study of children with developmental coordination disorder. Issue 1 (2nd January 2019) - Beernaerts, J.; Derie, R.; Nguyen, B.; Vansteenkiste, P.; De Baets, B.; Deconinck, F.J.A.; Lenoir, M.; De Clercq, D.; Van de Weghe, N.
Abstract: The Qualitative Trajectory Calculus (QTC) is a qualitative spatio-temporal calculus for describing interactions between moving point objects. So far, it remained unclear whether QTC is useful for describing subtle differences, such as between the movements of different parts of a human body. We tested the applicability of QTC to detect differences in the gait patterns of children with or without Developmental Coordination Disorder (DCD). We found that using a combination of three markers (i.e. ankle, toe and trochanter), QTC can achieve a high classification accuracy (i.e. 83.3%) of classifying subjects correctly to either the DCD group or the control group.